Gig workers, social protection and labour market inequality: lessons from Malaysia - Uchiyama, Yosuke; Furuoka, Fumitaka; Md Nasrudin Md Akhir (Penerbit Universiti Kebangsaan Malaysia, 2022)
The rise of the Gig Economy has created new concerns about inequality in rapidly digitising Asian economies. Whilst the emergence of the “on-demand economy” creates new opportunities for the youths and low-income groups, this has also created new policy challenges. As many use unofficial digital platforms and/or operate as unregistered self-run businesses, they remain outside the social protection system, leaving them especially vulnerable during times of crisis. This study therefore aims to provide new insights into this issue - social protection for gig workers – drawing upon the Malaysian experience. Using primary data collected through semi-structured interviews, we examine the working conditions of e-hailing drivers and online food delivery riders, two of the largest mainstream on-demand appbased gig workers’ groups in the country. The collected data were examined based on thematic analysis employing 15 subtopics and 3 main themes: (i) performance-based short-term decent work; (ii) platform and customer-centricity operations, and (iii) ecosystem for gig worker sustainability. From the perspective of gig workers, the study narrates their actual working conditions and perceived inequalities. Based on the findings, we conclude by critically reflecting on the potential for developing a worker-centred policy for social protection in the Gig Economy in Malaysia and elsewhere in Asia.